DETERMINATION OF PICTOGRAMS OF CARGO AIRSHIPS FOR USE IN LOGISTICS (Perner's Contacts, 2024)
The article discusses the categorisation of pictograms based on the type of carrier gas and the method of loading and unloading cargo in airships. The two primary carrier gases are helium and hydrogen. Cargo can be carried inside or outside the airship's hull, with further subdivisions based on loading and unloading capabilities. Finally, pictograms are assigned to each manufacturer based on their declaration as an example assignment
Keywords: airship; pictograms; logistics; airship manufacturers